Sistem Informasi Geografis Daerah Yang Layak Menerima Daging Qurban Di Wilayah Kota Padang - Sotar Sotar; Dani Mardianto (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2018)
Qurban is one of the worship that is held every year in the month dzulhijjah, the goal is closer to the creator. One of the functions of Qurban worship is as a form of concern to the dhuafa 'or the needy means that people who can slauchetering qurban animals can share the people who can not afford. In the city of Padang there are still many suburbs worthy of receiving Qurban meat, while in urban areas there are many sacrifices of Qurban animals and many excess meat quotas, but they only distribute them in urban areas with relatively good economy and certain orphanages, this results in the meat of Qurban accumulate in certain locations only. One of the causes of the Committee is difficult to get clear information about the location or area that really deserves the meat Qurban. The geographic information system built can provide solutions and information to the Qurban Committee or Mosque Board and other institution of Qurban meat distributor to the lack of information about the area, place, trip route, distance, number of people, the number of Qurban animals in each mosque in Padang city as well as areas categorized as worthy to receive the meat of Qurban. Thus the distribution of Qurban meat distributed evenly, the right target and the function of the Qurban worship achieved.